Analysis of Service Quality in Supporting The Effectiveness of Goods and Services Procurement - Mufidi, M. Syaif; Sukaris, Sukaris (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2023)
PT. Varia Usaha Fabrikasi is a labor service provider company, and is a limited liability company that is part of the extended family of PT Semen Indonesia Logistik Group. With high dedication and quality service products in all business activities, one of which is in the procurement of goods and services sector which is the company's main priority to achieve long-term corporate goals. Obstacles currently being faced regarding the large amount of competition in the procurement sector which makes business actors, especially PT. Varia Usaha Fabrikasi tries to emphasize the quality factor of the services provided in the hope of supporting the effectiveness of goods and services procurement activities. The research subject is the subject to be studied by the researcher. The type of research in this study is qualitative-descriptive because it utilizes qualitative data and is explained descriptively. Using the Snowball Sampling method found Sampling Subject 1 Users in the goods sector, Subject 2 Users in the services sector, and Subject 3 Users in the goods and services sector which has been suggested by the HR company PT. Varia Usaha Fabrikasi. Data were obtained from predetermined subjects by conducting interviews and direct observation to obtain the information needed by researchers to support this research. And the result is that the quality of service provided by PT. Varia Usaha Fabrikasi as a Provider is quite good and is considered quite effective in the procurement of goods and services both in terms of the process when carrying out the procurement and factors in the field